Peluang Bisnis Limbah Bonggol Jagung Menjadi Briket Pada Kelompok PKK Desa Mentasan - Dwi Sukowati; Herdian Farisi; Triat Adi Yuwono (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this community service is to assist the community in making briquettes from corncob waste and provide knowledge transfer about briquette product packaging and briquette marketing which can become a business opportunity for the PKK group in Mentasan Village, Cilacap Regency. The method used in carrying out this service is Participation Action Research (PAR). The PAR approach emphasizes solving problems and meeting the practical needs of the community, as well as producing knowledge. The problem that is being solved with the community is related to the accumulation of corncob waste and the production of knowledge in the form of briquette products as well as the transfer of knowledge about how briquettes can have business opportunities through stimulus through counseling on packaging and marketing of briquette products. The results of the dedication show that partners have been able to make corncob waste briquettes independently and have a better understanding of how to package and market briquette products.